Influence of Social Capital on Livelihood Outcomes for the Internally Displaced Persons in Kenya: A Social Capital Approach - Kiboro, Christopher Nkonge (European Scientific Journal, ESJ, 2017)
Social capital is increasingly recognized as important in influencing economic development, establishment of safe neighborhoods and wellfunctioning communities. There is growing evidence that communities with relatively higher stocks of social capital in form of grassroots associations appear to achieve higher levels of growth compared to societies with low stocks of social capital. This study sought to investigate the influence of social Capital on the livelihood outcomes for the internally displaced persons in Kenya. Membership to local level associations was used as a predictor of social capital. The study revealed that majority of the households that were affiliated to local level associations obtained essential services that influenced their livelihoods positively. Overall, the findings reveal that memberships in local associations (social capital) tend to insulate households from risks and other exigencies. The study recommends that government and other stakeholders such as non-governmental organizations should formulate projects and programs that seek to promote wider participation in local level associations particularly by the poor and those whose livelihoods are vulnerable.